E2F1 mediates sustained lipogenesis and contributes to hepatic steatosis - Denechaud, Pierre-Damien; Lopez-Mejia, Isabel C.; Giralt, Albert; Lai, Qiuwen; Blanchet, Emilie; Delacuisine, Brigitte; Nicolay, Brandon N.; Dyson, Nicholas J.; Bonner, Caroline; Pattou, François; Annicotte, Jean-Sébastien; Fajas, Lluis (The Journal of clinical investigation, 2016)
E2F transcription factors are known regulators of the cell cycle, proliferation, apoptosis, and differentiation. Here, we reveal that E2F1 plays an essential role in liver physiopathology through the regulation of glycolysis and lipogenesis. We demonstrate that E2F1 deficiency leads to a decrease in glycolysis and de novo synthesis of fatty acids in hepatocytes. We further demonstrate that E2F1 directly binds to the promoters of key lipogenic genes, including Fasn, but does not bind directly to genes encoding glycolysis pathway components, suggesting an indirect effect. In murine models, E2F1 expression and activity increased in response to feeding and upon insulin stimulation through canonical activation of the CDK4/pRB pathway. Moreover, E2F1 expression was increased in liver biopsies from obese, glucose-intolerant humans compared with biopsies from lean subjects. Finally, E2f1 deletion completely abrogated hepatic steatosis in different murine models of nonalcoholic fatty liver disease (NAFLD). In conclusion, our data demonstrate that E2F1 regulates lipid synthesis and glycolysis and thus contributes to the development of liver pathology.